Instrumented measures of sedentary behavior and physical activity are associated with depression among children and adolescents: a systematic review and dose–response meta-analysis of observational studies - Lu, Songtao; Sun, Jun; Guo, Zhiguang; Yi, Mingyu; Zhang, Yuheng; Wang, Jiali; Wang, Yue (Frontiers in Psychology, 2024)
Background: Higher sedentary behavior (SB) and lower physical activity (PA) are associated with negative physical and mental health outcomes. SB and PA can be objectively assessed using inertial sensors to evaluate body movements. This study aimed to quantify the association between instrumented measures of SB (i-SB) and PA (i-PA) and depression among children and adolescents using a systematic review and meta-analysis of observational studies. Methods: An electronic search was conducted on six databases up to May 12, 2024. A dose-response meta-analysis was conducted to determine the association between i-SB and i-PA and depression, expressed as odds ratios (ORs) and 95% confidence intervals (CIs). Results: Five cross-sectional and eleven longitudinal studies comprising 26,109 participants met the inclusion criteria. Comparing the most sedentary with the least sedentary groups of participants resulted in a pooled ORs of 1.05 (95% CI 0.94-1.16). Comparing the least active with the most active groups of participants resulted in pooled ORs of 0.93 (95% CI 0.84-1.07), 0.89 (95% CI 0.79-1.00), 0.83 (95% CI 0.66-0.99), and 0.73 (95% CI 0.58-0.89) for light, moderate-to-vigorous (MV), vigorous, and total PA, respectively. Robust error meta-regression analyses showed clear dose-response relationships between i-SB and i-MVPA and depression. Conclusion: Both i-SB and i-PA were significantly associated with risk of depression in children and adolescents, which may become non-significant after mutual adjustment for i-PA and i-SB.